(untitled) (Revista Română de Jurnalism și Comunicare, 2025)
In the current digital ecosystem, characterized by informational disorder, polarization, and the erosion of trust in institutions, the boundaries between reality and fiction are becoming increasingly blurred. The public sphere is marked by the presence of manipulative narratives, hard-to-identify informational actors, and technologies capable of simulating reality with deceptive fidelity (Harris, 2025; Saeidnia et al., 2025). In this landscape dominated by digital algorithms, automatically generated content, and accelerated virality, the present research investigates how communication specialists in Romania define, interpret, and evaluate the phenomenon of disinformation. The general objective is to identify the main vulnerabilities of the informational space, as well as to assess the effectiveness of current counter-strategies. To achieve this goal, a qualitative approach was used, based on 25 semi-structured interviews with specialists active in the academic, institutional, or media fields. The interviews focused on (1) defining the phenomenon, (2) mechanisms of dissemination, (3) effects at the individual, social, and political levels, as well as (4) evaluation of the effectiveness of countermeasures, with an emphasis on media literacy and the role of digital platforms. The results highlight the perception of disinformation as an intentional process, ideologically, economically, or politically motivated. Social networks are seen as the main channels of dissemination, through mechanisms such as echo chambers or recommendation algorithms. The effects include informational anxiety, distrust in institutions, polarization, and the destabilization of democracy. Fact-checking and media regulations are seen as short-term solutions, while media literacy is perceived as the most effective long-term approach. Thus, the conclusions support the need for public policies that include media literacy, the integration of critical thinking into education, and a rethinking of the responsibilities of digital platforms.